Fatal consequences of therapeutic thoracentesis in patients with systemic sclerosis - Sirotkin, Tsvi; Natour, Aiman; Wand, Ori; Levy, Yair (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
Systemic sclerosis (SSc) is a systemic autoimmune disease, characterized by systemic fibrosis and involvement of visceral organs. Pulmonary complications are common and a leading cause of death. Pleural effusions, however, are rare. Thoracentesis is a common procedure, performed to reveal the cause of pleural effusion or to drain it and relieve dyspnea. Although generally considered a low-risk intervention, complications of thoracentesis can lead to increased morbidity and mortality. We describe three patients with SSc and symptomatic pleural effusion who required thoracentesis. All patients deteriorated shortly after the procedure and died. We assume that patients with SSc are at high-risk to develop complications after thoracentesis, most likely due to the low compliant lungs and the low elastance of the pleura. In this population, thoracentesis should be done with high caution, while measuring the pleural pressure – invasively, or with noninvasive surrogates. Further studies are required to determine mechanisms of the complication